Analysis of Forage Yield and Nutritional Contents of Pennisetum glaucum (pearl millet) and Pennisetum purpureum (Napier grass) accessions - Animasaun, D. A.; Rathod, H. P.; Krishnamurthy, R. (Cuban Journal of Agricultural Science, 2018)
This study compared yield, nutrient compositions and forage quality of Napier grass (Pennisetum purpureum Schumach.) and pearl millet (Pennisetum glaucum L.) to determine their preference utilization as forage crops. Four accessions each of Napier grass and pearl millet were grown in the field with three replications in a Randomized Complete Block Design. Data were collected and analyzed on vegetative growth and yield parameters at 10 weeks after planting. Also nutrient composition of the shoot was determined. Napier grass grew more vigorously with significantly higher number of leaf/plant, leaf length and width. Meanwhile, plant height were similar (91.02 -111.95 cm) among the accessions bur for pearl millet IP17862 which had the least (82.82 cm). Napier grass accessions had significantly higher stem girth than the pearl millet. Mean tiller/plant was less than one in pearl millet and between 18.21-31.55 in Napier grass. Total soluble sugar and carbohydrate of the millet accessions were comparable with COM-CO3 and COM-CO4 Napier grass. Pearl millet NGB00551 was the richest in calcium (3.79 mg/g), potassium (0.36 mg/g), iron (0.52 ppm) and Zinc (0.60 ppm), however, IP17862 and COM-CO4 contained highest phosphorous and magnesium respectively. Dry matter percentage (DM), acid detergent fibre (ADF) and neutral detergent fibre (NDF) were higher in Napier grass than pearl millet accessions, but pearl millet accessions had more crude protein than the Napier grass. In overall, forage quality was higher in pearl millet accessions compared to Napier grass. Keywords: acid detergent fibre, dry matter yield, forage quality, neutral detergent fibre.